Dna isolation from human urine stain as an alternative material for personal identification examination - Yudianto, Ahmad; Sispitasari, Yeti Eka (Folia Medica Indonesiana, 2017)
Accurate determination of personal identity is crucial for an investigation since any inaccuracy may lead to fatal consequences in the judicial process. Identification through DNA analysis involves somatic chromosomes and mtDNA. Each part of the human body can be taken as a specimen since every nucleated cell in the body of an individual has identical DNA sequence. To date, samples for identification through DNA analysis are obtained from blood stains, semen stains, bones, vaginal swab, buccal swab etc. In certain cases, urine stains on the clothing have frequently been overlooked. So far, personal identification through DNA analysis by the use of urine stains has not been commonly carried out. The present study detected bands in the loci CSF1PO, THO1, TPOX and 106bp-112bp amelogenin in all samples visualized from the results of Polymerase Chain Reaction (PCR) with Polyacrylamid Agarose Gel Electrophoreses-silver staining for exposure durations of 1, 7 and 14 days. However, for exposure duration of 20 days (the maximum in the study), bands were only detected in the loci THO1 and TPOX in all samples (100%), whereas the loci CSF1PO and 50% amelogenin exhibited obvious bands. This indicated that DNA analysis of urine stains through detection of the locus STR CSF1PO, THO1, TPOX exhibited different detection responses for different exposure durations assigned to the samples of urine stain. Successful detection of these loci was supported by the differences in amplicon product and GC content at each locus. Of the loci studied, the ratio of GC content of the primers, sorted from the lowest, were as follows: locus CSF1PO of 42.6 1%, TPOX of 56.25%, and THO1 of 63.83%. In conclusion, the loci THO1 and TPOX had the same probability of success in the STR examination compared with the locus CSF1PO.